Sosialiasi Pemahaman Keseteraan Gender di Lingkup Sekolah Dasar Negeri 003 Desa Pulau Padang, Kecamatan Singingi, Kabupaten Kuantan Singingi, Provinsi Riau - Ismandianto I; Bilqhis Luthfiyya Syanura; Nailul Aflah; Elfikrah Rizyan Anugrah; Trysa Yulvarizal; Roni Matthew (Yayasan Daarul Huda Kruengmane, 2023)
Gender equality in the world of education is a crucial issue that impacts the social and economic development of society. This research aims to examine and analyze the status of gender equality at SDN 003 Pulau Padang Village, an elementary school located in the rural area of Riau. The research methods employed include surveys, classroom observations, interviews with students and school staff, as well as statistical data analysis. The results of this study highlight several challenges faced in achieving gender equality at SDN 003 Pulau Padang Village. Although the participation rates of female and male students in primary education are similar, there are significant differences in academic performance between the two groups. Further analysis reveals that factors such as social expectations, household roles, and access to educational resources play a crucial role in these differences. Furthermore, the research finds that efforts to enhance gender equality in schools have been made, including gender awareness programs and teacher training in inclusive approaches. However, there is still room for improvement in the implementation of these programs.